Surface Relief Gratings of Slide-Ring Hydrogels for Label-Free Biosensing - Aitor Cubells-Gómez; María Isabel Lucío; María-José Bañuls; Ángel Maquieira (Gels)
The creation of surface relief gratings using hydrogels for label-free biomolecule detection represents a significant advance in the development of versatile, cutting-edge biosensors. Central to this innovation is the formulation of materials with enhanced mechanical properties, especially for applications in soft, wearable technologies. In this work, we have developed novel biofunctional hydrogels that incorporate slide-ring supramolecular structures into their network, enabling the production of surface relief gratings with superior mechanical characteristics for biomolecule detection without the need for labels. These hydrogels, functionalized with bovine serum albumin and goat anti-rabbit antibodies, demonstrated excellent selectivity and sensitivity toward anti-bovine serum albumin and rabbit IgGs in blood serum, evaluated using a label-free format. Remarkably, the new materials matched the analytical performance of conventional hydrogels based on static networks while offering dramatically improved toughness and elasticity, with a compressive modulus comparable to human skin. This demonstrates the potential of slide-ring hydrogels for fabricating robust, label-free biosensing platforms. Furthermore, the flexibility of this system allows for the incorporation of various recognition elements tailored to specific applications.